2010
DOI: 10.1021/ac100222c
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Nonlinear Interferometric Vibrational Analysis of Lipids by Spectral Decomposition

Abstract: Unlike other CARS-based spectroscopy techniques, nonlinear interferometric vibrational spectroscopy (NIVS) is linear in analyte concentration and has a Raman lineshape free of non-resonant background distortions. We use spontaneous Raman scattering as a high accuracy benchmark for NIVS. As a challenging comparison, we examine spectra in the CH stretching region of 6 lipid samples. Singular value decomposition and reference to an independent chemical assay are used to directly compare NIVS and spontaneous Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The power of a spectral decomposition of the CARS image was recently pointed out and experimentally demonstrated. 38,39 Whereas the differences between lipid and protein spectra are substantial, the data set also contains spectral variations that are less dramatic, yet chemically meaningful. Differences in lipid composition, for instance, are manifested by relatively subtle spectral variations that may not be easily differentiated with a direct decomposition of the spectra.…”
Section: Discussionmentioning
confidence: 99%
“…The power of a spectral decomposition of the CARS image was recently pointed out and experimentally demonstrated. 38,39 Whereas the differences between lipid and protein spectra are substantial, the data set also contains spectral variations that are less dramatic, yet chemically meaningful. Differences in lipid composition, for instance, are manifested by relatively subtle spectral variations that may not be easily differentiated with a direct decomposition of the spectra.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that, with PCA, major constituents can be discriminated based on the correlated spectral variations within the dataset itself, thereby providing an unsupervised and effi cient assessment of chemical composition. On this note, the application of PCA for dimensionality reduction, in lieu of other nonlinear techniques, has been recently highlighted ( 34 ), and its utility for spectral decomposition and image reconstruction of hyperspectral CARS datasets has been illustrated in several studies ( 35,36 ), including our own work ( 32 ).…”
mentioning
confidence: 99%
“…NIVI was capable of differentiating normal and tumor tissues with >99 % confidence and of detecting the molecular tumor margin within 100 mm. It was shown that the NIVI spectra of biomolecules are equivalent to the corresponding Raman spectra and can be acquired up to 1,000 times faster than with spontaneous Raman microscopy, at comparable signal-to-noise ratios [31,34]. In the following sections, the theory, experimental setup, and demonstrated results of NIVI are covered in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been demonstrated in the quantitative analysis of lipid samples [31] and with molecular imaging of biological samples, including skin domains [32] and rat mammary tumor margins [33]. NIVI was capable of differentiating normal and tumor tissues with >99 % confidence and of detecting the molecular tumor margin within 100 mm.…”
Section: Introductionmentioning
confidence: 99%